International marketing, third edition - Paliwoda, Stanley; Thomas, Michael ([S.l.] : Butterworth-Heinemann, 1998)
The third edition of an established text, this book provides comprehensive treatment of international marketing issues and includes expanded coverage of Eastern Europe and the Pacific Rim. New for this edition are the expanded use of mini cases within the text to illustrate the latest developments in marketing, together with expanded coverage of: South East Asia and the Pacific Rim, Central and Eastern Europe, Globalization, Culture, Financial aspects of marketing. Included throughout are self-assessment and discussion questions, key terms, references and bibliography. Fully revised and updated edition of this established text Expanded coverage of Eastern Europe and the Pacific Rim Includes self-assessment and discussion questions, key terms and references.
Keywords: marketing